CORTICOSTEROID USE IN EARLY SYSTEMIC SCLEROSIS: INSIGHTS FROM THE TURKISH SYSTEMIC SCLEROSIS DATABASE - Ugurlu, Z.; Okyar, B.; Ersozlu, D.; Ozgur, D. S.; Bes, C.; Cefle, A.; Akdogan., A. (Elsevier, 2025)
[Abstract Not Available]
Keywords: Observational studies/registry; Glucocorticoids; Safety